Características físico-químicas da polpa do fruto de Couepia bracteosa Benth (Chrysobalanaceae), uma espécie subutilizada da Amazônia. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
Couepia bracteosa Benth. (Chrysobalanaceae), popularly known as pajurá, is a fruitful spe cies native to the Amazon. The fruits have pulp of sweetish flavor, thick and fibrous. In the Northern region the pulp is consumed mainly in the in natura form. The fruit processing al lows its use as an ingredient in various preparations, reducing its waste, providing healthy food and adding economic value to the species. In view of the above, the present study had as aim the determination of physical-chemical characterization and analysis of the antioxidant activity of the in natura and lyophilized pulp. The fruits are drupe-type globes, with a mean of 51,3% of pulp, characterized by low acidity, high percentage of sugars, high total fiber con tent, antioxidant capacity by DPPH and β-carotene/linoleic acid and absence of hemaglutinat ing activity. The pulp has an enjoyable aroma with high content of E,β-Ocimene, oleic acid as the major constituent of fatty acids, besides the presence of vitamin C, phenolic compounds and carotenoids. These results provide information that allows a better use of the fruit, which has potential application as a functional food in the agroindustry. The question of sustainabili ty is inherent to this research in two aspects: it is not necessary to overthrow the forest to study and investigate the physical and chemical properties of an Amazonian fruit and, on the contrary, the research proposed here, adds value to this raw material valuing the forest Which may encourage the cultivation of the species by family farmers.
Keywords: Alimentos – Composição; Valor Nutritivo de Alimentos; Frutas amazônicas; Pajurá; Crisobalanácea – Amazônia; Potencial antioxidante; CNPQ::CIÊNCIA DOS ALIMENTOS::FISIOLOGIA::; FISIOLOGIA AMBIENTAL; CIÊNCIA DOS ALIMENTOS::FISIOLOGIA